Communication challenges and experiences between parents and providers in South Korean paediatric emergency departments: a qualitative study to define AI-assisted communication agents - Meong Hi Son; Sejin Heo; Sohyeong Jeong; Hansol Paeng; Suyoung Yoo (BMJ Open)
Objectives This study aimed to explore communication challenges between parents and healthcare providers in paediatric emergency departments (EDs) and to define the roles and functions of an artificial intelligence (AI)-assisted communication agent that could bridge existing gaps.Design A qualitative study using in-depth interviews and affinity diagram methodology to analyse interview data.Setting A tertiary paediatric ED in South Korea.Participants 11 parents of paediatric patients and 11 ED staff members (physicians, nurses and security personnel).Primary and secondary outcome measures The study examined parent–provider communication difficulties, emotional responses and situational factors contributing to miscommunication and increased workload for ED staff.Results The study identified key emotional factors—fear, anger and sadness—that negatively affect communication between parents and ED staff. Parents experienced frustration due to uncertainty, insufficient information and difficulty navigating the ED process. ED staff faced challenges in managing anxious or demanding parents, resulting in increased workload and communication breakdowns.Conclusions An AI-assisted communication agent could help mitigate these challenges by providing timely information, managing non-medical inquiries and supporting both parents and ED staff at critical stages of the ED visit. Implementing such technology has the potential to improve communication and enhance overall patient care in paediatric emergency settings.